Comparing the effectiveness of different EGFR‐TKIs in patients with EGFR mutant non–small‐cell lung cancer: A retrospective cohort study in Taiwan. Issue 4 (7th January 2020) - Hsieh, Yao‐Yu; Fang, Wei‐Tse; Lo, Yu‐Wen; Chen, Yi‐Han; Chien, Li‐Nien
Abstract : The study was to compare the effectiveness of different epidermal growth factor receptor—tyrosine kinase inhibitors (EGFR‐TKIs) in patients with advanced non‐small‐cell lung cancer (NSCLC) and received EGFR‐TKIs as first‐line therapy. This retrospective cohort study was conducted using data from real‐world settings. Patients with stage IIIB and IV NSCLC and first received gefitinib, erlotinib, or afatinib between 2011 and 2015 were included. The date of the first claim for EGFR‐TKIs was set as the index date. Study endpoints were all‐cause death and treatment failure that was defined when patients added on or switched to chemotherapy or terminal care. A total of 5, 940 patients, including 3, 982 (67.0%) receiving gefitinib, 1, 207 (20.3%) receiving erlotinib, and 751 (12.7%) receiving afatinib, were eligible for this study. The 1‐year overall survival (OS) rates for gefitinib, erlotinib, and afatinib groups were 74% (95% confidence interval [CI]: 72–75%), 75% (95% CI: 73–77%), and 80% (95% CI: 77–83%), respectively. Compared to gefitinib, afatinib was associated with a lower risk of all‐cause death (adjusted hazard ratio [aHR] = 0.82, 95% CI: 0.72–0.93) but not erlotinib (aHR = 0.95, 95% CI: 0.86–1.05). Similar results were also found regarding the effectiveness of treatment. All the three EGFR‐TKIs showed no differences for both outcomes among patients with an Eastern Cooperative Oncology Group Performance Score of 2. The real‐world data exhibited afatinib was more likely to be used for younger patients in a better condition than other EGFR inhibitors, and observed prolonged OS and treatment effectiveness compared to gefitinib after performing a multivariate Cox regression analysis. Abstract : What's new? Patients in clinical trials have to meet specific criteria, but in the real world, doctors treat patients with a wide variety of age, comorbidities, and disease severity. In this paper, the authors sought to clarify criteria for selecting an EGFR‐TKI for lung cancer patients by collecting data from a real‐world patient cohort. They studied 5, 940 patients who received either gefitinib, erlotinib, or afatinib between 2011 and 2015. The patients receiving afatinib showed longer survival than those receiving gefitinib. However, it is noted that physicians tend to prescribe afatinib to younger or healthier patients, which may contribute to improved outcomes.